2017
DOI: 10.1111/jphd.12215
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum influence on interdisciplinary oral health education and practice

Abstract: Data supports that SFL is positively influencing oral health practice across professions, especially in areas of caries risk assessment and fluoride varnish application. SFL improves the frequency and quality with which DCPs and educators participate in oral health activities, and facilitates oral health inclusion in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…The barriers noted above point to opportunities that can maximize delivery of preventive oral health services to very young children. The push toward interprofessional education and practice, as well as medical and dental integration has been well described (27)(28)(29)(30). In addition to training physicians to provide oral health screening and apply fluoride varnish, two ideas that have been implemented at local and state levels include co-located services and care coordination.…”
Section: Discussionmentioning
confidence: 99%
“…The barriers noted above point to opportunities that can maximize delivery of preventive oral health services to very young children. The push toward interprofessional education and practice, as well as medical and dental integration has been well described (27)(28)(29)(30). In addition to training physicians to provide oral health screening and apply fluoride varnish, two ideas that have been implemented at local and state levels include co-located services and care coordination.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a 2012 national survey of oral health practices of pediatricians reported that while 41% of pediatricians agreed that they should apply fluoride varnish, 7% reported applying it to most patients eligible to receive it (Quinonez et al 2014). Strategies to increase the delivery of medical POHS include providing oral health training to primary care providers (Bernstein et al 2016; Dooley et al 2016; Clark et al 2017; Silk et al 2018), emphasizing the importance of POHS to providers (Dooley et al 2016), offering incentives to motivate staff to incorporate POHS into medical visits (Bernstein et al 2016), and reducing clinical workflow demands (Sengupta et al 2017). These strategies are most successful when tailored to a practice’s specific needs and when implemented together, addressing multiple barriers simultaneously (Bernstein et al 2016; Dooley et al 2016; Clark et al 2017; Silk et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Changes wrought by the pandemic and the evolving recognition of oral-systemic interactions (3,50) support increased interest in expanding the role of dentists. A growing emphasis on IPE and integration of oral health into primary care is evident in curriculum development, specific funding programs, and other efforts (51)(52)(53)(54)(55). Ongoing changes in dentistry and dental education are in keeping with these OP-PCP competency statement proposals: 2.20.2, participate in an interprofessional team approach that integrates oral health for the promotion and maintenance of overall health, and the prevention and treatment of disease; 2.24D.2, perform basic nutritional, safety, and other lifestyle counseling, including administration of vaccinations where permitted by law; and 2.24D.6, function effectively as medical team members in disaster relief efforts.…”
Section: Discussionmentioning
confidence: 99%